Analisis Penerapan Good Corporate Governance (GCG) Pada Bank Umum Syariah - Sri Endah Wahyuningsih; Isfandayani - (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2021)
This study aims to determine the analysis of the implementation of good corporate governance(GCG) in Islamic Commercial Banks, which is represented by Bank Syariah Mandiri and BankMuamalat Indonesia. This research method is included in qualitative research with a library researchapproach, namely a series of studies relating to library data collection methods. The results showedthat the implementation of GCG in BUS as represented by Bank Syariah Mandiri and Bank MuamalatIndonesia has implemented the principles of Good Corporate Governance (GCG) in accordance withthe prevailing laws and regulations, namely Bank Indonesia Regulation Number. 11/33 / PBI / 2009dated 7 December 2009 and Circular Letter (SE) of Bank Indonesia No. 12/13 / DPbS dated 30April 2010 concerning the Implementation of Good Corporate Governance for Sharia CommercialBanks (BUS) and Sharia Business Units (UUS), especially Article 62 and Article 63 concerning theobligations of Banks to submit GCG Implementation Reports to Bank Indonesia (BI) and stakeholders.other interests.